Satipatatana: Four Foundation of Mindfulness Program in Psychotherapy for Depressed Patients in Hua Hin Hospital - Em-on, Siriporn; Raksachom, Krissana; Kraijak, Orachon (Mahachula Academic Journal, 2024)
The study consisted of the following three objectives: 1) to investigate meditation practice based on the four foundations of mindfulness in Buddhist text; 2) to explore the psychotherapy approach by using Satipaṭṭhāna with depressed patients and propose a model for Hua Hin hospital; and 3) to examine the content validity index (CVI) of a psychotherapy model based on Satipaṭṭhāna with depressed patients in Hun Hin hospital. The study employed a qualitative research method by collecting data via documents and in-depth interviews. The content validity index (CVI) was assessed by seven experts and seven depressed patients. From the study, the following results are found: The concept of Satipaṭṭhāna and meditation practice based on Satipaṭṭhāna can be found in primary texts in great detail. Mahāsatipaṭṭhāna (the Four Foundations of Mindfulness) is concerned with the cultivation of mindfulness as the main path leading meditation practice to the attainment of the path, fruition, and Nibbāna. Mahāsatipaṭṭhāna can be divided into four foundations as follows: (1) Kāyānupassanā (contemplation of the body); (2) Vedanānupassanā (contemplation of feelings); (3) Cittānupassanā (contemplation of mind); and (4) Dhammānupassanā (contemplation of mind-objects). Satipaṭṭhāna relies on the continuous co-working between mindfulness and contemplation based on ātāpī, sampajāno, satimā (ardent, fully aware and mindful). Psychotherapy based on Satipaṭṭhāna with depressed patients should follow a continual practice of mindfulness in order to be mindful of what is happening in the moment. This will increase the practitioner's mindfulness and awareness, allowing him to recognize and manage the cycle of thoughts, emotions, and feelings. The following is a psychotherapy model based on Satipaṭṭhāna that specifies 7 times, 90 minutes of continuous practice, covering all 4 bases: the scale content validity index (S-CVI) of all seven experts is between 0.86 – 1.00. The mean of the content validity index is 0.94, while the content validity index of each item (I-CVI) is 0.94 and the average of the sum proportion of all experts is 0.94. After being assessed by all seven depressed patients, the content, psychotherapy model, and its application are at 1.00, indicating a very good level. The good rating is consistent with in-depth interviews with two groups: the expert group unanimously agrees that the content is academically correct and appropriate for both therapists and practitioners, and that it can be utilized to treat or lessen depression while also benefiting depressed patients, as does the depressed patient group, which unanimously agrees that a psychotherapy model allows one to understand methods and implement them appropriately while also benefitting negative emotional management in depressed patients.